Beginning Java EE 5 From Novice to Professional - Mukhar, Kevin. (Apress : Imprint: Apress, 2006)
Sun's new lightweight Java Enterprise Edition (EE) 5 is an extremely powerful platform for developing enterprise-level Java-based applications, primarily for the server. This book shows you how to harness that power, examining how the pieces of the new Java EE 5 platform fit together, including the redesigned annotations-driven EJB 3 spec as well as JavaServer Faces (JSF), integrated into the platform for the first time. Hands-on tutorials are also included, along with clear explanations and working code examples. You will grow to take the next step—from writing client-side desktop applications to writing enterprise applications. You will also learn how to use the individual APIs and tools in the Java EE 5 platform, and how to merge these to create your own enterprise applications.